2017
DOI: 10.3174/ajnr.a5296
|View full text |Cite
|
Sign up to set email alerts
|

Transient Focal Neurologic Symptoms Correspond to Regional Cerebral Hypoperfusion by MRI: A Stroke Mimic in Children

Abstract: Children who present with acute transient focal neurologic symptoms raise concern for stroke or transient ischemic attack. We present a series of 16 children who presented with transient focal neurologic symptoms that raised concern for acute stroke but who had no evidence of infarction and had unilateral, potentially reversible imaging features on vascular and perfusion-sensitive brain MR imaging. Patients were examined with routine brain MR imaging, MRA, perfusion-sensitive sequences, and DWI. Fourteen (88%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…This is earlier than described in other studies. [11][12][13] Each technique reviewed in this study provided data supporting the following pattern: apparent constriction of distal vessels on MRA, the presence of deoxygenated blood in cerebral veins on SWI, and initial hypoperfusion followed by a rebound hyperperfusion on ASL in the affected hemisphere. Patient 10 in this series demonstrated normal SWI and MRA findings and an ASL sequence with rCBF of only Ϫ0.4 at 4 hours, which may represent near-resolution of MR imaging perfusion changes or the transition from hypoperfusion to pseudonormalization during this patient's migraine.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…This is earlier than described in other studies. [11][12][13] Each technique reviewed in this study provided data supporting the following pattern: apparent constriction of distal vessels on MRA, the presence of deoxygenated blood in cerebral veins on SWI, and initial hypoperfusion followed by a rebound hyperperfusion on ASL in the affected hemisphere. Patient 10 in this series demonstrated normal SWI and MRA findings and an ASL sequence with rCBF of only Ϫ0.4 at 4 hours, which may represent near-resolution of MR imaging perfusion changes or the transition from hypoperfusion to pseudonormalization during this patient's migraine.…”
Section: Discussionmentioning
confidence: 67%
“…Many studies have suggested the implementation of ASL in the evaluation of children presenting with focal neurologic symptoms, each with the finding of initial hypoperfusion followed by delayed hyperperfusion. [11][12][13][14] Boulouis et al 11 published a case series exploring the use of the ASL MR imaging sequence in children, which demonstrated decreased regional cerebral blood flow when obtained Ͻ14 hours after symptom onset and increased regional cerebral blood flow when obtained Ͼ17 hours after symptom onset. Lehman et al 12 hours after symptom onset.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The AUC area of the MR SCALE-PWI sequence in the diagnosis of ischemic penumbra was 0.933. This indicates that MR SCALE-PWI has a good effect on the early identification of ischemic penumbra, which can reduce unnecessary treatment and prolong the time window for patients to receive recanalization or neuroprotective treatment [ 25 ].…”
Section: Discussionmentioning
confidence: 99%